The n-word : Les usages du mot “nigger” dans la littérature africaine américaine - Cyril Vettorato (Carnets)
Modern African American literature, birthed in the early twentieth century by W.E.B. Du Bois and other, more provocative authors such as Zora Neale Hurston or Langston Hughes, is intertwined with the development of political correctness in the United States. The way these writers use the word “nigger”, the most offensive among racial slurs, that African Americans have turned into a symbol of their identity, is a good illustration of that idea. The literary history of the twentieth century shows us that this word embodies the evolutions of the concept and the practice of black literature, as well as the way each writer invented his or her own way to deal with the legacies of History, crafting aesthetics which play with political correctness, violate it, or give it a new twist.